2022
DOI: 10.1002/cnma.202200269
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Assisted Fabrication of 2D Amorphous CeO2 and Its Application in Photoluminescence Enhancement

Abstract: Two‐dimensional (2D) non‐van der Waals (non‐vdW) amorphous nanomaterials have attracted much attention for optical, catalytic and biomedical applications owing to their rich dangling bonds and unsaturated coordination. CeO2, a typical non‐vdW material, with amorphous 2D structure and intrinsic optical properties have rarely been prepared via a top‐down method due to the lack of anisotropy in its 3D bonding network. Herein, we develop an environmentally‐friendly top‐down method to achieve ultrathin 2D amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For example, the exfoliation of non-vdW VO 2 and CeO 2 has been achieved with the assistance of SC CO 2 , which is much difficult than the case in vdW materials. [23,30] The strong breaking effect of SC CO 2 on interlayer chemical bonds reveals the different underlying mechanism in comparison with the other exfoliation methods. Furthermore, the amorphization of nonlayered PdCu alloy shows that SC CO 2 could lead to amorphization without exfoliation or vacancies, which provides new understanding of the SC CO 2 assisted process.…”
Section: The Investigation Of Amorphization Process In Sc Comentioning
confidence: 99%
See 3 more Smart Citations
“…For example, the exfoliation of non-vdW VO 2 and CeO 2 has been achieved with the assistance of SC CO 2 , which is much difficult than the case in vdW materials. [23,30] The strong breaking effect of SC CO 2 on interlayer chemical bonds reveals the different underlying mechanism in comparison with the other exfoliation methods. Furthermore, the amorphization of nonlayered PdCu alloy shows that SC CO 2 could lead to amorphization without exfoliation or vacancies, which provides new understanding of the SC CO 2 assisted process.…”
Section: The Investigation Of Amorphization Process In Sc Comentioning
confidence: 99%
“…Guo et al, for instance, fabricates the 2D amorphous CeO 2 with enhanced Photoluminescence. [23] Yan et al found the amorphization of non-vdW VO 2 (B) and TiO 2 in SC CO 2 . [24] What's more, they revealed that the amorphization in VO 2 originates from shear stress led by entropy deletion.…”
Section: D Amorphous Non-vdw Vo 2 Tio 2 and Ceomentioning
confidence: 99%
See 2 more Smart Citations